ULÍWMA BILIM BERIW MEKTEP OQÍWSHÍLARÍNDA KOMMUNIKATIVLIK KOMPETENCIYANÍŃ QÁLIPLESIW METODLARÍ - Utemuratov, B.K. (SCIENCE and SOCIETY, 2022)
The article gives recommendations on methods of forming communicative competencies of students of secondary schools, group work in the classroom.